Chapter Metaphors of art in the English translations of Giorgio Vasari's Le vite: a software-assisted enquiry - Luporini, Antonella (Lessico multilingue dei Beni Culturali, 2023)
This chapter focuses on the conceptual/linguistic metaphorical representations of the notion of 'art' in Vasari's Le Vite. It presents a case study of select concordances for «arte» extracted from the Italian LBC corpus, and a cross-linguistic comparison with the same segments taken from two English translations (de Vere 1912-1915 and Bondanella, Bondanella 1991). Firstly, six main metaphor categories are identified in the concordances from Le Vite. Two small parallel corpora are subsequently built, collecting the 'metaphorical' concordances from Le Vite and their corresponding translations, and analysed to assess if and how the original metaphors were transferred to the English texts. While both English translations maintain more than half of the original metaphorical occurrences, results also highlight interesting differences between the translators' approaches. Patterns from quantitative and qualitative investigation are discussed through select examples, considering both the functions of the original metaphorical categories and the effects of the translators' choices on their rendition. Finally, remarks are made about the contribution of (parallel) corpus techniques to metaphor translation analysis, as emerging from this case study.